Cognitive-Pragmatic Aspects of Gender Linguistics (Texas Journal of Multidisciplinary Studies, 2022)
The article deals with the issue of gender linguistics. Gender is studied as a social gender that determines the behavior of an individual in society, and how this behavior is perceived.